Effect of various cooling lubricant strategies on turning Inconel 718 with different cutting materials - Ostrowicki, Nicolai; Kaim, Alexander; Gross, Daniel; Hanenkamp, Nico (Procedia CIRP, 2021)
Due to its resistance to high temperatures and corrosion, Inconel 718 has a wide range of applications, particularly in the chemical and aerospace industry. The aim of this study is to investigate the potential of turning Inconel 718 with regard to tool life, depending on various cooling lubricant strategies and cutting materials. The reference process is flood cooling with carbide tools. Based on this, the process with carbide and CBN tools under dry machining, cryogenic cooling and cryogenic minimum quantity lubrication will further be investigated. Cutting forces, tool wear, roughness and chips are analyzed. Cutting length, surface quality and sustainability can be improved by using CBN and cryogenic minimum quantity lubrication (CMQL).<br
Keywords: Inconel 718; CBN; turning; cryogenic; cryogenic minimum quantity lubrication